Culturally responsive education as a sustainable educational approach: Reflections from primary school teachers' life science course practices - Emrullah Akcan (Journal of Pedagogical Research, 2022)
This paper aimed to determine primary school teachers' practices and classroom examples regarding culturally responsive education (CRE) in their life science courses. The study was conducted with the participation of 20 teachers, half of whom were employed in a primary school in Gaziantep province and the other half employed in the PIKTES [Promoting Integration of Syrian Kids into the Turkish Education System] project in the same province. The study adopts a qualitative research design that involves semi-structured interviews. The results revealed that the most common challenges experienced by primary school teachers were Syrian students' language and communication problems, as well as primary school teachers' lack of awareness about minority kids' culture and CRE. The most popular teacher techniques were those that aimed to increase student empathy. Based on the results, some suggestions were recommended for future studies.